Teacher Creativity Relationship with Interest Students Learning at SD Inpres Lolu During Pandemic - Azizah Azizah; Rizal Rizal; Agnes Priswi Yudtika; Melyani Sari Sitepu (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article aims to determine the relationship between teacher creativity and student interest in learning. The research design used is a type of qualitative research that is correlational. The research data was obtained through the distribution of a questionnaire containing some statements that were responded to by the respondents. The samples of this study were students of class VI, V, VI, and homeroom teachers of class IV, V, VI SD Inpres Lolu, totaling 74 students and 3 homeroom teachers. The data obtained were analyzed quantitatively using the Statistical Package for the Social Sciences (SPSS) version 23 software for windows. Based on the results of the correlation test, obtained the value of Sig. (2-tailed) of 0.355 > 0.05, it can be concluded that the null hypothesis (Ho) is rejected and accepts the alternative hypothesis (Ha). The results of this study indicate that there is a relationship between teacher creativity and student interest in learning.